Technology for Learners with Autism Spectrum Disorders - Ennis-Cole, Demetria Loryn. author. aut Link
XV, 99 p. 18 illus., 17 illus. in color.
Keywords: Technology for Learners with Autism Spectrum Disorders provides readers with an in-depth look at the characteristics of learners with ASD and explains how different forms of technology can be used to create learning opportunities for autistic students. The book is both an academic and practical to appeal to multiple audiences: researchers, parents, teachers, and therapists. Most literature on teaching children with ASD advocates for the use of schedules, structure, individualized instruction, techniques for transitioning, strategies for reducing problem behaviors, systematic instruction, vocational skill development, appropriate reinforcement, and environmental support. Specifically, designing learning environments that include these carefully crafted elements can address deficits in the areas of communication/language, behavior, and social skills. However, there is very little in the current educational literature which speaks to the types of academic activities that should be developed and used to help children with ASD gain skills in core academic areas, such as reading, writing, effective communication, and mathematics. This book fills that void by including sample academic activities—explaining strategies for working with children diagnosed with ASD, and examining ways a variety of technology tools can be used to both build skills and improve learning and understanding in children with ASD.